Research on the Constructed-Wetland/Regulation-Tank System at Pontificia Universidad Javeriana's Bogotá Campus - Torres, Andres; Galarza-Molina, Sandra; Lara-Borrero, Jaime; Forero, Javier (Journal of Sustainability Perspectives, 2024)
The stormwater harvesting (SWH) project at Pontificia Universidad Javeriana (Bogotá) began in 2007, initiated by the Water and Environmental Engineering research group (Ciencia e Ingeniería del Agua y el Ambiente), as part of PUJB's Environmental Management Plan and in collaboration with the University's Office of Physical Resources. This process included assessments of water supply and demand, rainwater quality, and financial and construction considerations. The system—a constructed wetland/regulation tank (CWRT)—collects rainwater runoff from the university's parking building (3,776 m²), the soccer field, and surrounding areas (14,816 m²). Beyond its hydrological performance, especially during periods of water scarcity, the system also functions as a full-scale laboratory to study biodiversity and ecological impacts in hydrological and hydraulic processes. The monitoring program, focused on changes in rainwater quantity and quality, has inspired several master's and doctoral research projects. These studies explore critical topics in urban hydrology, including stormwater harvesting, urban sediment management, real-time decision-making systems, and environmental and human health. This paper outlines the development of the stormwater harvesting system, shares the main findings from research projects, and discusses ongoing projects.